Legal Position of Syndicated Creditors in Submitting Claims on Debtors in the Application Process for Postponement of Debt Payment Obligations (PKPU) and the Legal Impact - Sianturi, Timotius Patrick Sianturi Patrick (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The arrangement of parties who can file claims in the process of suspension debt payment obligations has been regulated in Article 270 of Law number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The arrangement of parties who can file bills in the suspension of debt payment process still causes several problems in its implementation. This occurs in the suspension of debt payment process against debtors in syndicated loans which still creates uncertainty in its implementation because the suspension of debt payment Law does not specifically regulate it but only provides an explanation, so it is important to raise the issue regarding the party authorized to file claims against debtors in credit. Syndication. Meanwhile, the method used in this research is normative juridical research by examining library materials, namely the Civil Code and the suspension of debt payment Law. The suspension of debt payment Law has definitively determined the parties who can file claims, but to file claims in syndicated loans still creates dualism that arises due to the distinctive characteristics of syndicated loans, namely that there are agents who act as attorneys for syndicated participants to represent their interests. In principle, there is only one creditor in a syndicated credit agreement, namely a credit syndicate represented by an agent. Because the agent represents the interests of the syndicated participants, the agent has strong authority to take legal actions including submitting and registering claims to the Management in suspention of debt payment with the approval of the majority creditors.